Pendampingan Adaptasi Teknologi Pada Mata Pelajaran IPA di SMP Negeri Satap Padadita - Luhi, Bellavista Paulina; Saingo, Ririn Esna; Malo, Agnes Yuniati; Adindarena, Vindya Donna; Randjawali, Erwin; Tamu Ina, Anita (Welfare : Jurnal Pengabdian Masyarakat, 2023)
The Kampus Mengajar 4 program, which is carried out at SMP Satap Padadita, is expected to be able to advance the quality of education through the collaboration of students, subject teachers, and students in the classroom. The limited infrastructure in schools and the ability of teachers to utilize learning technology result in students being less interactive and quickly bored in carrying out learning. One of the programs that can be carried out is to provide assistance to teachers by utilizing technology to create an effective learning process in the classroom in science subjects. The method used is direct practice using learning support technologies such as PowerPoint and learning videos downloaded via YouTube, as well as direct observations outside the classroom. This hands-on practice was carried out in two classes, namely class VII-A with a total of 24 students and class VII-B with a total of 26 students, and was carried out in two meetings. The results obtained are that students become more active, happier, and better understand the learning material provided by the teacher.